KEARIFAN LOKAL DALAM PENGELOLAAN HUTAN DI DESA SERDANG KECAMATAN BARUSJAHE, KABUPATEN KARO - Karmila Br Ginting; Agus Purwoko; Junjungan Simanjuntak (Peronema Forestry Science Journal, 2015)
Management of forest resources is strongly influenced by local knowledge possessed the community to prevent the adverse effects on forests. This study was conducted to inventory of local knowledge related to trust or/and abstinence , ethics and rules, techniques and technologies, as well as the practices and traditions of forest management / land undertaken by the community in building and managing forests in Serdang village, sub-district of Barusjahe, Karo. This research was conducted in the village of Serdang District of Barusjahe , Karo in June to July 2014 The method used was a survey through interviews with respondents using questionnaires and direct observation and then the data is processed by descriptive qualitative method. The results showed that  the forms of local knowledge is still contained in Serdang village that can support forest management such as trust and/or customary restrictions such as the implementation of such ceremonial rites and ceremonies rebu rebu of year work, beliefs about village guards called "Pulu   2Balang", ethics and rules in the form of a ban on logging from protected forests, and capture fish by using  poison and bombs, ban hunting of protected animals, engineering and technology in the form of making firebreaks, pay attention to the wind direction before burning , no burning during the season dry , using bamboo as basket material and sunun, use bamboo as crutch of  plants, land management practices and traditions such as the division of an area into several land area to be planted with different agricultural commodities, applying intercropping techniques, use of the  compost and humus, knowledge of the crop cycle, the selection of appropriate agricultural commodities, as well as utilizing forest plants as a medicinal plant. This study also provides input for the government to continue to provide guidance and counseling for the community that local knowledge possessed people still evolving.Keywords: Local knowledge, community forest, village serdang, forest management